Chromium(II)-Catalyzed Amination of N-Heterocyclic Chlorides with Magnesium Amides - Steib, Andreas K.; Fernandez, Sarah; Kuzmina, Olesya M.; Corpet, Martin; Gosmini, Corinne; Knochel, Paul (Synlett, 2015)
We report a ligand-free chromium(II)-catalyzed amination reaction of various N-heterocyclic chlorides. CrCl2 regioselectively catalyzes the reaction of chloropyridines and dichloropyridines, dichloroquinolines, dichloroisoquinolines and dichloroquinoxalines with a range of aliphatic, allylic, benzylic and saturated (hetero)cyclic magnesium amides in the presence of lithium chloride as additive. The reactions were performed at 50 °C in THF and led to the desired aminated products in 56–96% yield.
Keywords: chromium; amination; magnesium amides; heterocycles; pyridine